A SOCIAL NETWORK APPROACH TO UNDERSTANDING COMMUNITY PARTNERSHIPS IN A NONTRADITIONAL DESTINATION FOR LATINOS. Issue 2 (March 2017) - Eiler, Brian A.; Bologna, Daniele A.; Vaughn, Lisa M.; Jacquez, Farrah
Abstract : Cincinnati, like other new migration areas, has recently experienced tremendous growth in the Latino immigrant population. Because greater health disparities exist for Latinos compared to both majority and other minority groups, it is essential to understand how migratory patterns and healthcare infrastructure are related. In this study, social network analysis (SNA), which quantitatively assesses and evaluates network formation and network relationships, was used to investigate the structure of the Greater Cincinnati Latino health network. Referral and collaboration networks were assessed for 29 individuals serving the Latino community. Results indicated the desired collaboration network was nearly twice as dense as either the physical or the mental health referral networks. The physical network was also denser than the mental health network. Similar results were found when analyzing network centralization. Taken together, results indicate a need for additional strategic partnerships between Latino‐serving providers and the Latino‐serving community. Specific recommendations are briefly discussed.